Description of two new species of Chiloglanis (Teleostei, Mochokidae) from the Eastern Zimbabwe Highlands freshwater ecoregion: an overlooked hotspot of rheophilic fishes - Tadiwa I. Mutizwa; Taurai Bere; Wilbert T. Kadye; Pedro H. N. Bragança; Albert Chakona (ZooKeys)
Growing evidence indicates that species diversity within the genus Chiloglanis Peters 1868 is poorly resolved and major taxonomic revisions are required. By integrating genetic and morphological analyses, this study describes two new Chiloglanis species from the Eastern Zimbabwe Highlands (EZH) freshwater ecoregion, a region that, until only recently, had been poorly-explored in terms of its ichthyological diversity. Chiloglanis asperocutis Mutizwa, Bragança & Chakona, sp. nov. is distinguished from other southern African congeners by a combination of characters, including ridge-like tubercles distributed on the dorsal and lateral surfaces of the head and body giving the skin a conspicuously rough texture, ten closely packed mandibular teeth, deeply forked caudal fin and a high number of primary premaxillary teeth (68–128). Chiloglanis compactus Mutizwa, Bragança & Chakona, sp. nov., attains the smallest size (> 46 mm SL) of all currently known congeners in southern Africa. It is distinguished from all the other congeners from the region by a combination of characters; the possession of seven pectoral fin rays, conical tubercles distributed across the dorsal and lateral surface of the head and body, eight widely spaced mandibular teeth, a shallow forked caudal fin with rounded lobes, a low number of primary premaxillary teeth (31–53) and fewer dorsal fin rays (5). These two species are distributed in both the Buzi and Pungwe River systems. The study is the first in a series of publications that will provide formal descriptions of a number of deeply divergent lineages (candidate species) identified in previous studies from southern Africa. The persistence of the unique riverine fauna in the EZH is threatened by multiple impacts that are altering the hydrological regime of the rivers and streams as well as habitat degradation and excessive sedimentation from gold panning and agricultural activities.